2001
DOI: 10.1128/mcb.21.11.3738-3749.2001
|View full text |Cite
|
Sign up to set email alerts
|

PGC-1-Related Coactivator, a Novel, Serum-Inducible Coactivator of Nuclear Respiratory Factor 1-Dependent Transcription in Mammalian Cells

Abstract: The thermogenic peroxisome proliferator-activated receptor ␥ (PPAR-␥) coactivator 1 (PGC-1) has previously been shown to activate mitochondrial biogenesis in part through a direct interaction with nuclear respiratory factor 1 (NRF-1). In order to identify related coactivators that act through NRF-1, we searched the databases for sequences with similarities to PGC-1. Here, we describe the first characterization of a 177-kDa transcriptional coactivator, designated PGC-1-related coactivator (PRC). PRC is ubiquito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
324
1
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(334 citation statements)
references
References 32 publications
5
324
1
4
Order By: Relevance
“…PGC-1a was originally cloned from brown adipose tissue on the basis of its interaction with PPARc [1]. The avPGC1a cloned here from chicken skeletal muscle, unlike the subfamily of PGC-1a, PGC-1b [28] or PGC-1-related coactivator (PRC) [29], includes motifs specific to PGC-1a in similar positions as described in the following ( Fig. 2A): An activation domain, including the LXXLL motif (aa 142-146), which is common to PRC, and three consensus sites for phosphorylation by protein kinase A (aa 237-240, 371-375, and 653-656) are well conserved; in contrast the arginine of codon 173 and the alanine of codon 329 in the mouse and rat PGC-1a are deleted in bird.…”
Section: Discussionmentioning
confidence: 99%
“…PGC-1a was originally cloned from brown adipose tissue on the basis of its interaction with PPARc [1]. The avPGC1a cloned here from chicken skeletal muscle, unlike the subfamily of PGC-1a, PGC-1b [28] or PGC-1-related coactivator (PRC) [29], includes motifs specific to PGC-1a in similar positions as described in the following ( Fig. 2A): An activation domain, including the LXXLL motif (aa 142-146), which is common to PRC, and three consensus sites for phosphorylation by protein kinase A (aa 237-240, 371-375, and 653-656) are well conserved; in contrast the arginine of codon 173 and the alanine of codon 329 in the mouse and rat PGC-1a are deleted in bird.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in the expression of all three of these factors have been shown to modulate mitochondrial biogenesis activity. 19,[22][23][24] RT-PCR analyses revealed that the expression of NRF-1 and TFAM was markedly higher in the majority (eight of 10) CLL patients as compared to the normal lymphocytes, whereas the expression of PRC appeared unchanged in all cases (Figure 2b). Considering that NRF-1 activates the transcription of TFAM, it is not surprising that TFAM expression would also be elevated in cells with higher basal NRF-1 expression.…”
Section: Elevated Mrna Expression Of Mitochondrial Biogenesis Factorsmentioning
confidence: 99%
“…PGC-1s: meet the parents PGC-1α was first identified in a yeast two-hybrid screen for factors that interact with the nuclear receptor PPARγ in brown adipose tissue (BAT) in the context of cold-induced thermogenesis [1]. Soon after, two homologous genes, PGC-1β [6] and PRC [7] were cloned by cDNA and protein sequence homology, respectively. Although these proteins are encoded by different genes, their modular structure is remarkably similar [8], which explains the partial overlap in their physiological roles [3].…”
Section: Introductionmentioning
confidence: 99%